2010
DOI: 10.1080/14999013.2010.534958
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity and Other Psychometric Properties of the Short-Term Assessment of Risk and Treatability (START) in a Norwegian High Secure Hospital

Abstract: Short-to medium-term risk assessment in psychiatric hospitals is a topic of clinical relevance that deserves attention from the research community. In this paper, the Short Term Assessment of Risk and Treatability, or START (Webster, Martin, Brink, Nicholls, & Middleton, 2004), a new structured instrument for judgment of dynamic risk and treatment factors is briefly described. Internal reliability properties are analyzed and the predictive validity for severe violence in a Norwegian high secure psychiatric hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 17 publications
4
55
1
Order By: Relevance
“…Nonstad et al (2010) found that patients showed increases in strengths and decreases in vulnerability over the course of treatment. In addition, Wilson et al (2010) found that START scores performed particularly well in predicting aggression over periods of nine months or less compared to a longer-term period of 12 months.…”
Section: Taking Stock: the State Of Adolescent Violence And Recidivismentioning
confidence: 99%
See 1 more Smart Citation
“…Nonstad et al (2010) found that patients showed increases in strengths and decreases in vulnerability over the course of treatment. In addition, Wilson et al (2010) found that START scores performed particularly well in predicting aggression over periods of nine months or less compared to a longer-term period of 12 months.…”
Section: Taking Stock: the State Of Adolescent Violence And Recidivismentioning
confidence: 99%
“…Research shows that both START total scores and overall risk estimates predict aggression towards others, including physical aggression and violence, verbal aggression, aggression towards objects, and sexually inappropriate behavior (Braithwaite, Charette, Crocker, & Reyes, 2010; Chu, Thomas, Ogloff, & Daffern, 2011; Desmarais, Nicholls, Wilson, & Brink, 2012; Gray et al, 2011; Nonstad et al, 2010; Nicholls et al, 2006; Wilson, Desmarais, Nicholls, & Brink, 2010). Moreover, they also have been shown to predict a broader range of outcomes, such as self-harm (Gray et al, 2011; Nicholls et al, 2006), substance use (Braithwaite et al, 2010), victimization (Gray et al, 2011), self-neglect (Gray et al, 2011), and unauthorized leave (Braithwaite et al, 2010; see also Nicholls et al, 2006).…”
Section: Taking Stock: the State Of Adolescent Violence And Recidivismentioning
confidence: 99%
“…However, only a handful of studies have examined the reliability and validity of START assessments (Braithwaite, Charette, Crocker, & Reyes, 2010: Chu et al, 2011; Gray et al, 2011; Nicholls, Brink, Desmarais, Webster, & Martin, 2006; Nonstad et al, 2010). The original validation study was published by Nicholls and colleagues (2006).…”
Section: Short-term Assessment Of Risk and Treatabilitymentioning
confidence: 99%
“…The START is intended to be used for short-term assessments of acute risk and is repeated bimonthly. In recent studies the START strengthsscale (the total score of the strength side of all items) showed to be predictive of less violence in the short-term and of successful community reintegration (Braithwaite et al, 2010;Nonstad et al, 2010;Viljoen, Nicholls, Greaves, De Ruiter, & Brink, 2011;Wilson, Desmarais, Nicholls, & Brink, 2010).…”
Section: Assessment Tools For Protective Factorsmentioning
confidence: 99%